Micropropagation of Centella asiatica L. An Important Medicinal Herb (Progressive Agriculture, 2013)
High frequencies of multiple shoot regeneration were achieved from shoot tip explants cultured on MS media fortified with 4.0 mgl-1 BAP + 0.1 mgl-1 NAA. On an average 10.2?0.38 shoots per explant were obtained. The regenerated shoots were rooted in MS medium supplemented with 1.0 mgl-1 IBA. The in vitro grown plantlets were acclimatized and successfully transferred to natural condition with 80% survival. A reproducible protocol was established for in vitro propagation through multiple shoot induction of Centella asiatica L. an important medicinal herb having high medicinal value.DOI: http://dx.doi.org/10.3329/pa.v19i2.16928 Progress. Agric. 19(2): 51 - 56, 2008